2023
DOI: 10.3389/fspor.2023.1021757
|View full text |Cite
|
Sign up to set email alerts
|

The effects of upper and lower limb elastic band training on the change of direction, jump, power, strength and repeated sprint ability performance in adolescent female handball players

Abstract: This study aimed to examine the effects of incorporating 10-week elastic band strength training (EBST) program on change of direction, jumping ability, repeated sprint ability, and both muscular strength and power in adolescent female handball players. Participants aged 15.8 ± 0.2 years were divided by playing position, and players from each position were then randomly assigned between the elastic strength (n = 17) and control (n = 17) groups. The experimental group performed periodized upper and lower-body el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
2
4
0
Order By: Relevance
“…The lower limb muscle strength performance in lateral jumping was found to be of great significance in potentially enhancing the stability of the participants. This result is similar to that in some of the literature [25,26,31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The lower limb muscle strength performance in lateral jumping was found to be of great significance in potentially enhancing the stability of the participants. This result is similar to that in some of the literature [25,26,31].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the ASTP had a stabilizing effect on the muscles. This stability was produced by the activation of many highly coordinated muscles, as different jumping methods recruit different numbers of muscles [31]. A curve graph of the force plate results showed that the muscle strength of the participants' lower limbs increased, the force exerted on the ground by jumping with the left and the right foot increased, and the reaction force obtained by both feet could instantly maintain stability and allow for the next jump to be continued.…”
Section: Discussionmentioning
confidence: 99%
“…One such increasingly popular training method is elastic band training, offering versatility and accessibility for resistance training. It provides various benefits, including accommodating resistance, enhancing joint stability, and increasing muscle activation [ 8 12 ]. Recently, researchers and practitioners have explored diverse elastic band training variations to maximize its effectiveness and tailor it to specific athletic needs [ 8 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite extensive studies on elastic band training in various athletic populations [ 8 , 9 , 14 , 15 ], limited research has focused specifically on its effects on adolescent female handball players. Understanding the potential benefits and distinctions between standard elastic band training and contrast elastic band training in female handball players is essential for development of an evidence-based training programme that optimizes their athletic performance.…”
Section: Introductionmentioning
confidence: 99%
“…This can help in improving their jump shooting accuracy. Jumping is an important part of handball (Gaamouri et al, 2023). By practicing jumping consistently, players can improve their ability to jump high, which is crucial in scoring goals or blocking opponents' attacks.…”
Section: Introductionmentioning
confidence: 99%